PREMENSTRUAL SYNDROME (PMS) – A REVIEW OF PHARMACOLOGICAL AND NON-PHARMACOLOGICAL TREATMENT APPROACHES - Aleksandra Białas; Weronika Lusarczyk; Natalia Sapeda; Aleksandra Młocek; Adrianna Truszyńska-Zawisza; Zuzanna Romanowska; Karolina Gorczyca; Kamil Kerknawi; Paulina Mikulec; Emilia Loch (International Journal of Innovative Technologies in Social Science, 2025)
Premenstrual Syndrome (PMS) and its severe form, Premenstrual Dysphoric Disorder (PMDD), are prevalent cyclical disorders affecting the emotional, behavioral, and physical well-being of women of reproductive age. This review aims to present an overview of the current understanding of PMS/PMDD and critically examine both pharmacological and non-pharmacological treatment methods. Based on recent clinical trials and systematic reviews, selective serotonin reuptake inhibitors (SSRIs), hormonal therapies, and emerging drugs like sepranolone and ulipristal acetate demonstrate efficacy in symptom reduction (Bäckström et al., 2021; Comasco et al., 2020; Maranho et al., 2023). Simultaneously, cognitive-behavioral therapy (CBT), mindfulness-based interventions, nutritional supplements, herbal medicine, and even open-label placebos are gaining attention as effective non-pharmacological alternatives (Frey Nascimento et al., 2025; Reilly et al., 2023; Shojiasi et al., 2024; Sultana et al., 2022). Despite promising findings, further high-quality research is needed to tailor personalized and integrative treatment strategies.